Existence Results of Random Impulsive Integrodifferential Inclusions with Time-Varying Delays - Sahar M. A. Maqbol; R. S. Jain; B. S. Reddy (Journal of Function Spaces)
This study examines the existence of mild solutions for nonlinear random impulsive integrodifferential inclusions with time-varying delays under sufficient conditions. Our study is based on the Martelli fixed point theorem, Pachpatte’s inequality, and the fixed point theorem due to Covitz and Nadler. Besides, we generalize, extend, and develop some well-known results in the existing literature.